If it's not what You are looking for type in the equation solver your own equation and let us solve it.
42x-56=4x+4
We move all terms to the left:
42x-56-(4x+4)=0
We get rid of parentheses
42x-4x-4-56=0
We add all the numbers together, and all the variables
38x-60=0
We move all terms containing x to the left, all other terms to the right
38x=60
x=60/38
x=1+11/19
| 3n+4n=14+5n | | X+1/3=3-x+5/4 | | 1/2(x+7)+1=-11 | | s-27/8=6 | | -6x^2+18x=27x+75 | | –8=–2(q−5) | | 34 =m+41 | | 5y-9=8y+9 | | 4m+5=-5m-13 | | 4(-3x-1)=-(x+1 | | t+13=2 | | 6-4a+4=7+a | | 11x-(8x-4)=13 | | R(11)=(x+1)(x-3) | | 3x+13+8+16x=154 | | 3=12x^2+1.2x+2 | | 8=k+74 | | 6p+5=41 | | 4w^2-7w-8w=3 | | N(10)=35-x | | 6-4a4=7+a | | 7-x=45 | | (7x-15)+(x+23)=180 | | .21P=P(2^-x) | | 1+5k=-3k-16 | | -2+4n=58 | | 116 =n+97 | | {q}{4}=10 | | -7p-10=-52 | | -3x=68 | | -3(x+5)=3x(x-1) | | (4x+14)+(2x+52)=360 |